The Effectiveness of Aquaponic Systems with Different Types of Plants on the Water Quality of Fish Culture Media - Irfan Zidni; Iskandar Iskandar; Achmad Rizal; Yuli Andriani; Rian Ramadan (Jurnal Perikanan dan Kelautan, 2019)
This study aims to determine the effect of aquaponic systems with different types of plants on the water quality of sangkuriang catfish (Clarias gariepinus) aquaculture. This research was conducted from June to August 2018 at the Ciparanje Fish Farming Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran. The fish used were sangkuriang catfish seeds (Clarias gariepinus) aged 54 days with a length of 5-7 cm and a weight of 5 grams that were kept in a 1 m2 fibre container with a density of 100 individuals/fiber. Plant growth media used using gutters with an area of planting media that is 0.8 x 0.3 m. The method used in this study is an experimental method using a Completely Randomized Design (CRD) with four treatments and four replications. Treatment A (Spinach plants), Treatment B (Pakcoy plants), Treatment C (Lettuce), and Treatment D (control). The parameters observed in this study were water quality, which included dissolved oxygen content, pH, temperature, ammonia, nitrate, and phosphate. The research data were analyzed using Variance Analysis with a level of 5% and continued with Duncan's multiple range test while the water quality data were analyzed descriptively. The results showed that the values of temperature, dissolved oxygen, and pH were 25.1-27.0oC, 6.3-7.5 mg / L, 7.0-7.8. The lowest ammonia value was found in treatment A using water spinach that is equal to 0.001 mg/L.